2003
DOI: 10.1007/s00425-003-1117-1
|View full text |Cite
|
Sign up to set email alerts
|

Transforming petals into sepaloid organs in Arabidopsis and oilseed rape: implementation of the hairpin RNA-mediated gene silencing technology in an organ-specific manner

Abstract: Oilseed rape ( Brassica napus L.) genotypes with no or small petals are thought to have advantages in photosynthetic activity. The flowers of field-grown oilseed rape form a bright-yellow canopy that reflects and absorbs nearly 60% of the photosynthetically active radiation (PAR), causing a severe yield penalty. Reducing the size of the petals and/or removing the reflecting colour will improve the transmission of PAR to the leaves and is expected to increase the crop productivity. In this study the 'hairpin' R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 42 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…Whilst the vegetative structure of the plant contributes towards increased pod production by providing more sites at which pods can be formed, it can also reduce the amount of incident light reaching photosynthetic components lower down in the canopy. Even the relatively small petals are believed to block out~60% of the photosynthetically-active radiation (PAR) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the vegetative structure of the plant contributes towards increased pod production by providing more sites at which pods can be formed, it can also reduce the amount of incident light reaching photosynthetic components lower down in the canopy. Even the relatively small petals are believed to block out~60% of the photosynthetically-active radiation (PAR) [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, possible that the strict tissue specificity of the low-seed-gossypol trait observed in cotton may, in part, be due to the fact that silencing does not spread in cotton tissues. A similar tissue-specific confinement of silencing has been observed in Arabidopsis and oilseed rape in experiments involving conversion of petals into sepals through RNAi (40). A lack of systemic silencing or a highly restricted spread of silencing has also been noted in several other plant systems (41,42).…”
Section: Discussionmentioning
confidence: 56%
“…In Arabidopsis floral formation, the combined functions of the A-type, B-type and E-type MADS box genes lead to the formation of petals. A recent paper showed that the Atype MADS box gene APETALA1 (AP1) promoter regulated the expression of ihp RNA genes homologous to the respective B-type MADS box genes APETALA3 and PISTILATA (AP3, PI), showing the suppression of petal formation and the emergence of double sepals in flowers of transgenic Arabidopsis (Byzova et al 2004). Therefore, a combination of organ-specific target gene expression and another organ-specific promoter regulating RNAi enables a more confined spatial disruption of the target mRNA expression and is useful for the dissection of gene function for organ formation.…”
Section: Tissue-specific Rnai Vectorsmentioning
confidence: 99%